LV Septum Pacing Shown Safe, Feasible Alternative for Antibradycardia Pacing - Mosley, Mary (MD Conference Express, 2015)
Left ventricular septum pacing is feasible and may be an alternative site for antibradycardia pacing that avoids some of the disadvantages associated with biventricular pacing. This article reviews the early investigational research and a feasibility study supporting this potential new approach.